Effect of cations on microbial aggregation using brevibacillus panacihumi strain ZB1, lysinibacillus fusiformis strain ZB2 and enterococcus faecalis strain ZL - Alias, Muhammad Anwar (2015)
Microbial aggregation and surface hydrophobicity are two important variables often used to evaluate the initial stage of granules development. Most studies only focused on the development of granules but have not studied the ability of microbial aggregation and surface hydrophobicity (SHb) of bacteria in the initial stage of biogranulation process. This study investigated the effect of metal cations in improving granules development based on microbial aggregation and surface hydrophobicity (SHb). Autoaggregation (AAg) and SHb of Brevibacillus panacihumi strain ZB1, Lysinibacillus fusiformis strain ZB2 and Enterococcus faecalis strain ZL cells were studied using batch culture. Synthetic wastewater under aerobic condition with the addition of Ca2+, Mg2+, Al3+, Mn2+ and Zn2+ was applied. Initial screening for AAg and SHb using 2-level factorial design showed that Ca2+ caused a significant increase in these two parameters for all the bacteria. Based on the AAg ratio measured from changes in absorbance of the culture medium, all of the three bacteria were classified as medium AAg. L. fusiformis strain ZB2 had the highest value of AAg by having a compact and large microscopic clustering of cells, followed by B. panacihumi strain ZB1 and E. faecalis strain ZL. The AAg ability of each bacterium was well correlated with the SHb. Addition of selected mixed cations (Ca2+, Mg2+, Al3+and Mn2+) increased the AAg ability of the bacterial strains from 35% to 41% for E. faecalis strain ZL, 43% to 56% for B. panacihumi strain ZB1, and 49% to 57%, for L. fusiformis strain ZB2. The SHb of the investigated bacteria had also increased from 32% to 37% for E. faecalis strain ZL, 45% to 55% for B. panacihumi strain ZB1, and 51% to 57%, for L. fusiformis strain ZB2. Addition of mixed cations has also caused a significant increase in the microbial aggregation and SHb of the mixed bacterial culture. The mixed culture consisting of all bacteria had the highest microbial aggregation (44.7%). On the contrary, the mixed culture consisting of B. panacihumi strain ZB1 and E. faecalis strain ZL had the highest SHb (28.8%). As a conclusion, addition of different cations resulted in an increase of AAg and SHb in individual and consortium of the tested bacteria.